Practices of fault diagnosis in household appliances: Insights for design. (20th August 2020) - Pozo Arcos, Beatriz; Bakker, Conny; Flipsen, Bas; Balkenende, Ruud
Abstract: Fault diagnosis is the process of identifying and characterising a fault when a failure occurs. It is, therefore, an essential step to take before product-repair. In this study, we ask how conventional users diagnose faults in household appliances and how the design of these appliances facilitates or hampers the process of fault diagnosis.To investigate this we qualitatively analyse the content of iFixit's online repair forum for three products: kitchen blenders, vacuum cleaners, and refrigerators. First, we develop a conceptual analysis framework based on the literature. Second, using conventional content analysis, we correlate facilitating and hampering features with the appliances' design. The process of fault diagnosis can be described by the subsequent actions of fault detection, fault location and fault isolation. Our results show that consumers detect faults by noticing five types of symptoms. Subsequently, two distinct diagnosis approaches can be distinguished. One follows a trial and error approach where the user performs diagnosis actions which usually result in replacing a potentially defective component until the symptoms disappear. The other occurs when the symptoms are error codes; the defective part can be more accurately identified, and the diagnosis is straightforward. The results also show that appliances are not designed to make fault diagnosis easy. Access to and visibility of components are often blocked, making fault isolation challenging. User manuals commonly lack relevant explanations, for instance when symptoms are different from error codes. Based on these findings, we propose a number of design recommendations to facilitate fault diagnosis for household appliance users. Highlights: Current design features of appliances make fault isolation challenging. Trial-and-error is mostly used by users to diagnose failures in household appliances. Product disassembly is usually required for fault diagnosis. Two different fault diagnosis approaches are identified, with and without error codes.